Anonymous job applications and hiring discrimination - Ulf Rinne (IZA World of Labor, 2014)
Anonymous job applications to combat hiring discrimination are gaining attention and interest. Results from a number of field experiments in European countries (France, Germany, the Netherlands, and Sweden are considered here) shed light on their potential to reduce some of the discriminatory barriers to hiring for minority and other disadvantaged groups. But there are also some cautions to consider.
Keywords: J71; J78; M51; 330; discrimination; hiring; job applications; Europe